1997
DOI: 10.1002/mrm.1910370113
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised, automated segmentation of the normal brain using a multispectral relaxometric magnetic resonance approach

Abstract: The purpose of this study was the development and testing of a method for unsupervised, automated brain segmentation. Two spin-echo sequences were used to obtain relaxation rates and proton-density maps from 1.5 T MR studies, with two axial data sets including the entire brain. Fifty normal subjects (age range, 16 to 76 years) were studied. A Three-dimensional (3D) spectrum of the tissue voxels was used for automatic segmentation of gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF) and for cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 23 publications
3
82
0
2
Order By: Relevance
“…An evaluation of the ICV estimation procedure yielded an error for the IC volume of less than 1.5% (Hentschel and Kruggel, 2004). Phantom-based validation studies (Alfano et al, 1997) found a variance of 2.6 -3.2% between phantom volumes and segmented compartments. From retest experiments using a segmentation approach similar to the one applied here, the mean and the variance of the difference between volumes from different scans were 0.4% resp.…”
Section: Discussionmentioning
confidence: 96%
“…An evaluation of the ICV estimation procedure yielded an error for the IC volume of less than 1.5% (Hentschel and Kruggel, 2004). Phantom-based validation studies (Alfano et al, 1997) found a variance of 2.6 -3.2% between phantom volumes and segmented compartments. From retest experiments using a segmentation approach similar to the one applied here, the mean and the variance of the difference between volumes from different scans were 0.4% resp.…”
Section: Discussionmentioning
confidence: 96%
“…[10][11][12] Rather than using images, this new technique defines the tissue types of the brain as specific combinations of these 3 parameters and can thereby synthesize tissue maps, 13 similar to the Alfano method. [14][15][16] In this way, the major components of the ICV (gray matter, WM, and CSF) can be defined by physical properties rather than by relative image characteristics. The use of such tissue maps makes it possible to perform fully automated calculation of BPF without the need for manual postprocessing.…”
mentioning
confidence: 99%
“…This is often the case in MR image classification where many unknown brain tissue clusters may be present. Nevertheless, unsupervised methods are generally preferred because they appear to be successful in clinical environments for classification of normal brain data and often have clear characteristic knowledge (22). But, difficulties also arise in the pathological cases which contain unknown complex knowledge (23,24).…”
Section: Unsupervised and Supervised Methods In Multispectral Mr Clasmentioning
confidence: 99%